Threats and harassment of public health officials in the United States during the COVID-19 pandemic: insights from the adaptive leadership framework - Jeffrey Glenn; Mirabella A. Keogh; Katelyn N. Aldridge (International Journal of Public Health, 2026)
Objectives Many public health officials faced threats and harassment while doing their jobs during the coronavirus disease 2019 (COVID-19) pandemic. The Adaptive Leadership Framework (ALF) serves as a useful lens through which the dangers of exercising leadership in a crisis situation can be analyzed and understood. Methods This study employed a systematic qualitative media content analysis to examine U.S. newspaper coverage of public health officials during the COVID-19 pandemic. We identified articles using Newspaper Source Plus and Newswires (EBSCO) databases and then screened and coded them using a deductive approach guided by the ALF. A total of 50 articles were analyzed using directed thematic analysis. Results Media coverage revealed widespread and multifaceted resistance to public health leadership during the pandemic. Opposition originated from both the public (e.g., harassment, threats, and protests) and authority figures (e.g., firing). Despite these challenges, public health officials demonstrated adaptive leadership behaviors, particularly maintaining stability and building strong partnerships. Conclusion Threats and harassment reflected broader institutional and political pressures, underscoring the importance of institutional protection and leadership preparation for future public health crises.